2007
DOI: 10.2174/138161207781662894
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Receptors as Potential Targets for Novel Anti-Platelet Agents

Abstract: Platelets have important roles in atherosclerosis and thrombosis and their inhibition reduces the risk of these disorders. There is still a need for platelet inhibitors affecting pathways that reduce thrombosis and atherosclerosis while leaving normal hemostasis relatively unaffected, thus reducing possible bleeding complications. Although combinations show progress in achieving these goals none of the present inhibitors completely fulfill these requirements. Collagen receptors offer attractive possibilities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 91 publications
(127 reference statements)
1
25
0
Order By: Relevance
“…12 Thus, platelet collagen receptors, and especially GPVI, have emerged as a highly interesting target for novel antiplatelet drugs. 13 Recent advances in mRNA and protein analysis are expected to significantly contribute to a better understanding of the fundamentals of platelet biology. Because platelets do not have a nucleus, proteomics technology is the method of choice to provide data on protein expression in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…12 Thus, platelet collagen receptors, and especially GPVI, have emerged as a highly interesting target for novel antiplatelet drugs. 13 Recent advances in mRNA and protein analysis are expected to significantly contribute to a better understanding of the fundamentals of platelet biology. Because platelets do not have a nucleus, proteomics technology is the method of choice to provide data on protein expression in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…The next most abundant receptor is GPIbα, the von Willebrand receptor, and inhibitors have been discovered and used in animal models of thrombosis [162]. Other receptors include the collagen receptors α 2 β 1 and GPVI [163], and PAR-1, the thrombin receptor [164]. As discussed above, FcRIIa is an important receptor for the interaction of DENV with platelets, and small molecule inhibitors of this receptor have been discovered [165].…”
Section: Targeting the Platelet In Vhfmentioning
confidence: 99%
“…This makes the receptor as well as the associated signaling pathways attractive as therapeutic targets. 8 Indeed, one of the 9 proteins found in higher abundance upon GPVI ligation, aldose reductase, is the kind of protein one would like to "discover" with a differential proteomic approach. Functional investigations revealed that inhibition of aldose reductase impaired GPVI-induced platelet aggregation.…”
Section: Org Frommentioning
confidence: 99%
“…While initially it was believed that the reason for the different subunits in the immunoproteasome was to optimize peptide generation during antigen processing for MHC class I presentation, recent evidence suggests that additional roles exist for the immunoproteasome including cytokine production. 8 Amazingly, the use of proteasome-specific inhibitors demonstrates that the cellular processes controlled by each proteasome are in part distinct as selective inhibition of the constitutive proteasome does not affect IL-23 production in monocytes. 8 However, these selective inhibitors do not induce apoptosis when used individually, 6 thus overlapping functions are likely to exist as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation